Pengendalian Penyakit Busuk Buah Phytophthora pada Kakao dengan Cendawan Endoft Trichoderma sp. di Desa Sidomulyo, Kecamatan Lebakbarang Kabupaten Pekalongan - Muhammad Malik Madani (Jurnal Pusat Inovasi Masyarakat (PIM), 2019)
Phytophthora (BBP) rot caused by Phytophthora palmivora is an important disease that plays a role in decreasing cocoa production. The use of endoft fungus Trichoderma is done to control this disease. Community service aims to find biological agensts that are easily obtained and applied by farmers and have a high level of effectiveness so that it can reduce the severity of cocoa pod rot in the village of Sidomulyo. Trichoderma is found in nature and must be explored first using bamboo, rice and litter media. The results of the exploratory fungus were then tested for effectiveness using dual culture and then applied directly to plants. Exploration of trichoderma fungi with green morphological characteristics. The results of the effectiveness test showed that trichoderma has the potential to be a biological agenst of fruit rot control in cocoa as evidenced by direct testing in the field and the results of a decrease in severity of up to 40% were obtained.